Plate 1: Various chemical apparatus and instruments - Accum, Friedrich Christian (An Explanatory Dictionary of the Apparatus and Instruments Employed in the Various Operations of Philosophical and Experimental Chemistry, 1824)
Depicts an assortment of chemical apparatus and equipment, including glass bottles, alembics, and flasks, as well as funnels, adopters, cupels, crucibles, muffles, blowpipes, eudiometers, syringes, siphons, spirit and chemical lamps, dropping tubes, and freezing apparatus. A gun-barrel apparatus, which is "a gun-barrel when combined with a furnace," is also shown in figure 42.
Keywords: Chemistry; Chemical apparatus